Revolutionizing Customer Service : The Impact of Large Language Models on Chatbot Performance - Sudeep Meduri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the transformative impact of Large Language Models (LLMs) on customer service chatbots across various industries. Through a comprehensive analysis of case studies, the article explores the implementation strategies, performance metrics, and technological advantages of LLM-powered chatbots in sectors including e-commerce, telecommunications, financial services, healthcare, and travel. The article highlights the advanced capabilities of LLMs in natural language understanding, response generation, and continuous learning, demonstrating their potential to significantly enhance customer interactions and operational efficiency. The article also addresses key technical challenges in implementing LLM chatbots, such as data privacy, response accuracy, and scalability, offering potential solutions for each. Finally, it discusses future directions for LLM-powered chatbots, including multimodal capabilities, emotion recognition, and predictive customer service, providing insights into the evolving landscape of AI-driven customer engagement.